Landscape Pattern Impacts on the Population Density and Distribution of Black Shama (Copsychus cebuensis Steere) in Argao Watershed Reserve, Argao, Cebu, Philippines. (13th August 2013) - Malaki, Archiebald Baltazar B.; Cruz, Rex Victor O.; Bantayan, Nathaniel C.; Racelis, Diomedes A.; Buot, Inocencio E.; Florece, Leonardo M.
Abstract : This study determined the impacts of landscape pattern on population density of C. cebuensis within AWR, a conservation priority in Cebu, Philippines. Three land uses were identified, namely, (a) cultivated (3, 399 ha/45%); (b) forestlands (3, 002 ha/40%); and (c) build-up (1, 050 ha/15%). Forest patches at class have irregular/complex shapes; thus the forest areas in AWR are more fragmented and heterogeneous. Estimated population density of C. cebuensis was 52 and 53 individuals per hectare in mixed and natural forests. There were only three predictors at the landscape and four at the sampling site level, respectively have able to explain the behavior of the population density of C. cebuensis . Relative humidity and canopy cover were having high positive significant correlations while tree basal area has high negative correlation (at landscape). Elevation and canopy cover have positive high significant and significant correlations, while slope and shrub cover have negative significant correlation with C. cebuensis population density. The adjustedR 2 values were 0.345 and 0.212 (at landscape and sampling site). These suggest that about 34.5% of the variations of the population density of C. cebuensis have been accounted for by the former and only 21.2% by the latter. Preservation and protection of remaining forest fragments within AWR are paramount.